Tingkat Religiusitas dan Pendapatan: Analisis Pengaruh Terhadap Keputusan Membayar Zakat, Infaq dan Shadaqah - Okta Yuripta Syafitri; Najla Wildan; Nurul Huda; Nova Rini (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims is to examine the factors that influence the decision of individual to pay zakat, infaq and sadaqah. These study researchers using two factors, namely religiosity and income level. Respondents of this research were people from Jakarta, Bogor, Depok and Tangerang, (Jabodetabek) Indonesia. Data was collected based on survey results from the distribution of questionnaires to 100 respondents and tested using PLS-SEM analysis. The path coefficient test results indicate the value of T statistics for religiosity is 2,407, which means that religiosity, has a significant effect on the decision to pay ZIS. While T statistics for the income level showed a result of 4,715. Based on these results it can be seen that the level of income has more significant effect on the decision to pay ZIS. Therefore, it can be concluded that the level of income has more significant effects on paying ZIS decisions than the effect of religiosity.